The Cultural and artistic environment of Transcarpathia in the interwar period and its influence on E. Kontratovych - Cheipesh, Anna; Havrosh, Oksana (Art and Design, 2025)
The research relevance is determined by the need to determine the impact of the complex socio- economic circumstances of the interwar period and the cultural revival of Transcarpathia on the formation of Ernest Kontratovych’s creative outlook. The study aimed to analyse the formation and rise of the cultural and artistic centre in Transcarpathia and to characterise its influence on E. Kontratovych. The methodology involved the use of historical, biographical, analytical, and several art historical methods, which were used to comprehensively characterise the historical context and development of the cultural sphere in Transcarpathia during the specified chronological period. These methods were also used to analyse the artistic environment of E. Kontratovych and demonstrate its impact on the selection of themes and motifs in the early stages of creative career. The article examined the development of the cultural environment in Transcarpathia during the interwar period, which influenced the formation of Kontratovych’s artistic style and the selection of subjects and themes in the early phases. A significant amount of factual material was gathered concerning the artistic and cultural life of Subcarpathian Rus in the 1920s and 1930s. The influence of the environment on Kontratovych’s thematic choices and the development of the plots was substantiated. The conclusions drawn from the research contribute to determination of the development of cultural and artistic processes in Transcarpathia in the 20th century. A substantial portion of the historiographical and factual material is valuable for scientific research, museum work, and the creation of textbooks, curricula, and lecture courses.